2016
DOI: 10.1080/00365521.2016.1218541
|View full text |Cite
|
Sign up to set email alerts
|

Development of psoriasis in IBD patients under TNF-antagonist therapy is associated neither with anti-TNF-antagonist antibodies nor trough levels

Abstract: Anti-TNF-induced psoriasis seems to be independent of anti-TNF antibodies and trough levels. Interruption of Anti-TNF therapy is rarely necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
3
23
1
Order By: Relevance
“…Contrary to the trend in older literature, most studies do not report an association with female gender, race, or body mass index (BMI), suggesting a possible reporting bias in previous studies. 8,12,[17][18][19][20][21]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to the trend in older literature, most studies do not report an association with female gender, race, or body mass index (BMI), suggesting a possible reporting bias in previous studies. 8,12,[17][18][19][20][21]…”
Section: Resultsmentioning
confidence: 99%
“…An association with complicated IBD phenotype was found, although this could possibly represent confounding by indication, as patients with more difficult to treat CD (upper GI tract and perianal disease) and UC (pancolitis) are more likely to receive anti-TNF-a therapy. 16,18,20 The same is true for a shorter duration of disease, as this could indicate a more aggressive phenotype, requiring biological therapy. 8…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Adult data are mixed. Afzali et al reported that patients who developed psoriasis had increased clinical IBD activity, while Protic et al reported little to no IBD activity at time of psoriasis, including no change in inflammatory markers …”
Section: Discussionmentioning
confidence: 99%